2018
DOI: 10.18203/issn.2455-4510.intjresorthop20183671
|View full text |Cite
|
Sign up to set email alerts
|

Cruciate retaining versus posterior-stabilized total knee arthroplasty: a short-term comparative study

Abstract: <p class="abstract"><strong>Background:</strong> Total knee arthroplasty has got excellent results. Among the techniques (posterior-stabilized vs posterior cruciate retaining total knee arthroplasty) it is unclear whether one design has superior outcome over another. The purpose of the present study was to directly compare clinical and radiological outcomes of these two designs.</p><p class="abstract"><strong>Methods:</strong> A prospective study involving 36 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…These results are comparable with the studies done by N Li et al (9) , Matsumoto et al (10) , Yagishita et al (11) Berick et al (12) ; where they also indicated more significant improvement in ROM in PS TKA as compared to CR TKA. The mean objective knee score in the present study for CR and PS prosthesis was 33.17 and 39.1 respectively which got improved to 71.17 and 73.13 which indicated significant improvement but in contrast to Suthar RK et al (13) , Longo UG et al (14) study; favours PS prosthesis with better objective knee score results.…”
Section: Discussioncontrasting
confidence: 58%
“…These results are comparable with the studies done by N Li et al (9) , Matsumoto et al (10) , Yagishita et al (11) Berick et al (12) ; where they also indicated more significant improvement in ROM in PS TKA as compared to CR TKA. The mean objective knee score in the present study for CR and PS prosthesis was 33.17 and 39.1 respectively which got improved to 71.17 and 73.13 which indicated significant improvement but in contrast to Suthar RK et al (13) , Longo UG et al (14) study; favours PS prosthesis with better objective knee score results.…”
Section: Discussioncontrasting
confidence: 58%